Computational fluid dynamics analysis in the ductless whole-house air conditioning system - Tasaka Rie; Kindaichi Sayaka; Nishina Daisaku; Maeoki Mitsuhiko (E3S Web of Conferences, 2020)
Recently, the heat load for space heating in residential houses has been reduced as airtightness, and thermal insulation performance has been improving even in moderate climate regions of Japan. In such situations, the heat load can be handled by one room air-conditioner with high energy efficiency. We report the results of computational fluid dynamics (CFD) analysis of an indoor thermal environment and the airflow distribution during the space heating operation in a ductless house air conditioning system, in which heated air from a room air conditioner installed in a thermal-insulated basement space is distributed throughout the building using air inlets on the floor in each story and open-door rooms without ductworks. To determine the adequate size and position of the air inlets on the floor in this heating system, we evaluated the air circulation performance for changes in the conditions of the air inlets by CFD analysis for a standard two-storey house model in Japan. The results suggest that the air temperature distribution is markedly different in the size and position of the air inlets on the floor. Large volumes of airflow through the openings in the building resulted in maintaining the rooms at a temperature range of 17 to 24 degrees uniformly. These results also provide information for system and building designs for effective space heating and for proper usage when choosing to open or close air inlets in the operational phase.